Usage of Financial Services in South Africa: Perceptions Matter - Philip Kostov; Thankom Arun; Samuel Annim (Institute for the Study of Labor (IZA), 2013)
This study investigates the access to and usage of financial services in South Africa. Financial services are categorised in three types namely; general accounts and services, investment/savings and insurance/assurance. Taking into account the interactions between usage of different types of financial services, we use multivariate simultaneous probit specification to examine the effect of financial perception. Our results suggests that after controlling for endogeneity of choices and a range of control variables, financial perceptions are robust determinant of access to financial services. The impact of financial perception however reduces and gradually disappears as one moves up the financial access ladder towards more advanced financial products and services. In a policy context, targeting demand-side factors to increase access to and use of financial services is advisable. This targeting however can only be successful if it is tuned to specific basic financial services and products.
Keywords: O16; N27; R20; 330; financial; perception; behaviour; general accounts; investment; insurance; South Africa